2009
DOI: 10.1007/s11738-009-0299-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation from axenic explants of Lilium oxypetalum (D. Don) Baker, an endemic bulbous plant of high altitude Himalaya

Abstract: In vitro propagation protocol for Lilium oxypetalum, a high altitude Himalayan endemic lily, has been developed. Effect of explant types (i.e., callus and in vitro bulblet scales) and sucrose concentration [0-6.0% (w/ v)] on in vitro bulblet regeneration of L. oxypetalum was tested in previously optimized Murashige and Skoog basal medium supplemented with 2.0 lM 6-benzyladenine and 0.1 lM a-naphthaleneacetic acid. Callus explants produced significantly (P \ 0.01) higher number of bulblets per explant than bulb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…In vitro adventitious bud regeneration from scales of Lilium rely on many factors like cytokinin and auxin concentrations such as BA and NAA and sucrose concentration (Varshney et al 2000;Kumar et al 2005). Many previous studies found that bulblet growth was favorable when using a high concentration of sucrose in the growth medium (Joshi and Dhar 2009;Bakhshaie et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro adventitious bud regeneration from scales of Lilium rely on many factors like cytokinin and auxin concentrations such as BA and NAA and sucrose concentration (Varshney et al 2000;Kumar et al 2005). Many previous studies found that bulblet growth was favorable when using a high concentration of sucrose in the growth medium (Joshi and Dhar 2009;Bakhshaie et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Generally 1/2 to full concentration of salt were used and 30 gl -1 sucrose was added to culture medium for shoot proliferation (Faisal et al 2006). In a procedure for rooting of shoots, reduced concentration of medium salt and sucrose were used (Khan et al 1999;Singh et al 2008) However, in bulbous plants, high concentration of culture medium salt and sucrose was oftenly applied to produce more shoots and increase bulblet growth (Takayama and Misawa 1983;Bonnier and Van Tuyl 1997;Hu et al 2006;Joshi and Dhar 2009). In this study, shoot number and fresh weight per explant had increased significantly on medium containing double strength of LS salt and 50 gl -1 sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…The formation and development of bulblets are crucial in the life cycle . Despite lots of literature on micropropagation of Lilium (Joshi and Dhar, 2009;Saadon and Zaccai, 2013), the physiological and biochemical mechanisms governing bulblet development remain unclear. Much evidence has shown that HA favors plant growth in many ways but is limitedly used in bulbous crops including in vitro.…”
Section: Discussionmentioning
confidence: 99%